KCNC2 variants of uncertain significance are also associated to various forms of epilepsy - Seiffert, Simone; Pendziwiat, Manuela; Hedrich, Ulrike B. S.; Helbig, Ingo; Weber, Yvonne; Schwarz, Niklas (Frontiers in Neurology, 2023)
Recently, de novo variants in KCNC2, coding for the potassium channel subunit KV3.2, have been described as causative for various forms of epilepsy including genetic generalized epilepsy (GGE) and developmental and epileptic encephalopathy (DEE). Here, we report the functional characteristics of three additional KCNC2 variants of uncertain significance and one variant classified as pathogenic. Electrophysiological studies were performed in Xenopus laevis oocytes. The data presented here support that KCNC2 variants with uncertain significance may also be causative for various forms of epilepsy, as they show changes in the current amplitude and activation and deactivation kinetics of the channel, depending on the variant. In addition, we investigated the effect of valproic acid on KV3.2, as several patients carrying pathogenic variants in the KCNC2 gene achieved significant seizure reduction or seizure freedom with this drug. However, in our electrophysiological investigations, no change on the behavior of KV3.2 channels could be observed, suggesting that the therapeutic effect of VPA may be explained by other mechanisms.